Folk High School as a Supportive Environment for Participants with High-Functioning Autism - Joel Hedegaard; Martin Hugo; Cecilia Bjursell (AS: Andragoška Spoznanja)
The aim of this article is to explore the Folk High School as a supportive environment for participants with neuropsychiatric functional impairments, primarily high-functioning autism, from the perspectives of the participants, the staff, and the principals. The participants’ perspective consisted of 21 interviews, the teachers’ perspective was observed in three focus-group interviews, and the principal’s perspective through 19 telephone interviews. Folk High School is shown to be supportive because it: (i) creates a safe and caring environment, (ii) places the individual participant at the centre of its operations, and (iii) is based on the provision and articulation of clear structures. A limited focus on the classroom and the course content is too narrow for a group of individuals with high-functioning autism. It is important to examine the relationships between different categories of workers and how they, in an interwoven symbiotic system, can provide the participants with the best possible conditions for learning.